INTEGRASI MEDIA DIGITAL DAN PERMAINAN EDUKATIF DALAM PEMBELAJARAN BILANGAN CACAH KELAS V SD - Lirra Zanni; Yeni Rahmawati; Siti Inganah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology has significantly influenced mathematics learning in elementary schools. This study aims to describe the integration of digital media and educational games in teaching whole numbers to fifth-grade students. Using a descriptive qualitative approach, the research was conducted at SD Negeri Kedungsari in November 2025 with 17 participants. Data were collected through participatory observation, documentation, and teacher reflection notes, and analyzed using Miles and Huberman’s interactive model. The integration process involved four stages: planning, implementation, collaboration, and evaluation. Digital applications such as Quizizz, Wordwall, and Math Games were combined with contextual educational games, including place-value pocket activities. Findings revealed that 88% of students showed positive responses to digital media, while 82% benefited from educational games. The results of student understanding were very positive, the results of the T test showed that the Sig. value was 0.176 (> 0.05) which means there was a significant difference between the pretest and posttest (before and after using digital media and educational games). The results demonstrate that combining digital media and educational games enhances motivation, collaboration, and numeracy skills. This study highlights the importance of innovative, technology-based approaches to strengthen foundational mathematics learning in Indonesian elementary schools.